TI_GERICHTE 11.2004.124 vom 12. November 2004 , beneficio d'inventario: proroga del termine per decidere l'accettazione dell'eredità - TI Tribunale d'appello (2004)
beneficio d'inventario: proroga del termine per decidere l'accettazione dell'eredità